Frecuencia de parásitos intestinales y su relación con los factores desencadenantes en escolares del sector rural del cantón Balsas - Rivas Feijoo, María Esther (2013)
The parasitosis affects to millions of people, harming the economic development of the nations, and they are closely linked with the poverty and the most abandoned social sectors, the prevalence is bigger in children for the lack of natural or acquired resistance. The present investigative work determined the frequency of intestinal parasites and its relationship with the factors triggers in school of the rural sector of the Canton Balsas, by means of the study of descriptive type, of traverse court that was carried out it in 6 schools belonging to the rural places of the Canton Balsas in which a total of 219 children and girls participated to which were carried out an analysis Coproparasitario and a survey was also applied the family parents to know the main factors triggers .You concluded that the parasitosis is of 58% being more frequent in women with 52%, likewise the parasitosis was observed with more frequency in children and girls from 10 to 11 years with a percentage of 32% being the most frequent parasites Entamoeba histolytica con 30% and Entamoeba Coli with 16%, de me was also identified it lacks of drinkable water and to the inadequate elimination of served waters they are the main factors triggers of parasites. Key words: Parasitosis, children and girls, factors triggers